Association Between Perinasal Uptake on Radioactive Iodine Whole-Body Scan and Nasolacrimal Duct Obstruction - Minjung Seo; Hongje Lee; Na Ri Park; Ju-Hyang Lee; Seol Hoon Park (Medicina)
Background and Objectives: This study reports an association between nasolacrimal duct obstruction (NLDO) and perinasal uptake on radioactive iodine (RAI) whole-body scan. Materials and Methods: This is a retrospective study of 37 patients from May to November 2017 who underwent thyroidectomy and I-131 ablation for papillary thyroid cancer (PTC) and had a follow-up I-123 diagnostic WBS and dacryoscintigraphy. Ophthalmic examinations assessed punctal stenosis, NLDO, tear film break-up time, Schirmer’s test, punctate keratopathy, tear meniscus height, epiphora, and ocular dryness. Perinasal and nasal uptake on whole-body scans (WBSs) were assessed as negative (no uptake) or positive (focal uptake). The associations between perinasal uptake on WBS, dacryoscintigraphy findings, and ophthalmic assessments were assessed. Results: Nasal uptake on I-131 post-ablation WBS were observed in 60 eyes (81%); perinasal uptake was observed in 8 eyes (11%). Nasal uptake on I-123 post-ablation WBS were observed in all eyes; perinasal uptake was observed in 15 eyes (20%). Perinasal and nasal uptake on I-131 post-ablation WBS were significantly associated with delayed excretion on dacryoscintigraphy (p < 0.001 and p = 0.03, respectively). Perinasal uptake on I-123 WBS was associated with both abnormal dacryoscintigraphy findings and ocular dryness (p < 0.001 and p = 0.02, respectively). Conclusions: Perinasal uptake on I-131 post-ablation and I-123 diagnostic WBS was significantly associated with delayed excretion on dacryoscintigraphy, suggesting NLDO.